Development of Transformative Leadership for Head of State Madrasah Aliyah - Hasanah, N Dewi; Badrudin, Badrudin; Sanusi, Hary Priatna (Al-Hayat: Journal of Islamic Education, 2023)
Leadership is an essential element in organizational speed. Mastery of leadership theory can make a significant contribution to the madrasah principal. This research aims to examine the influence of the transformative leadership of madrasah heads on teacher performance in two madrasahs in Bandung. This research uses a qualitative approach. Collecting data with interview techniques, observation, and documentation. Informants in this study involved the head of the madrasah, the deputy head of curriculum, teachers and students. Data analysis techniques include data reduction, presentation, conclusions, and validity testing. The study results show that the madrasah principal uses a leadership strategy that builds teacher commitment through regular supervision and monitoring. The madrasah head provides inspirational communication, motivates teachers with the afterlife goals, and instils discipline through habits. In dealing with criticism, the madrasah principal is open and democratic and involves all madrasah members in policy-making. This transformative leadership approach shows a constructive and honest intellectual stimulus. The head of the madrasa awards teachers who excel and offers advice to teachers who need it. This research emphasizes the importance of transformative leadership in improving the quality of teachers and realizing Madrasahs that are akhlakul karimah.